2016
DOI: 10.1007/s00214-016-1807-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of single water molecule on proton transfer reaction in uracil dimer cation

Abstract: Ionizing radiation to DNA induces sometimes the DNA damage. In this report, the ionization dynamics of uracil dimer (U) 2 and its water complex (U) 2 -H 2 O have been investigated by means of direct ab-initio molecular dynamics (AIMD) method in order to elucidate the effects of single water molecule on the reaction rate of proton transfer (PT) in DNA model base pair. The (U) 2 dimer is widely used as a simplified mimetic model of Watson-Crick base pair. The static ab-initio calculation showed that two conforme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…They concluded that the rate constant of ESPT was larger when water took place of the H‐bonded ether since the H‐bond formation with water strengthened the proton‐accepting ability of the water chain. Tachikawa studied the ionization dynamics of uracil dimer and its water complex (U) 2 ‐H 2 O by using direct ab initio molecular dynamics (AIMD) method for expounding the effect of single water on the rate of PT. Their results showed that the reaction rate of PT was evidently influenced by the position of H 2 O around U 2 .…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the rate constant of ESPT was larger when water took place of the H‐bonded ether since the H‐bond formation with water strengthened the proton‐accepting ability of the water chain. Tachikawa studied the ionization dynamics of uracil dimer and its water complex (U) 2 ‐H 2 O by using direct ab initio molecular dynamics (AIMD) method for expounding the effect of single water on the rate of PT. Their results showed that the reaction rate of PT was evidently influenced by the position of H 2 O around U 2 .…”
Section: Introductionmentioning
confidence: 99%